Estrategias financieras y competitividad en las pymes del sector metalmecánico / Financial Strategies and Competitiveness for Pymes in the Metallurgy Sector - Rincón, Hilda; Cherema, Norma; Burgos Tovar, José (Impacto Científico, 2020)
ResumenEl objetivo fundamental del artículo fue determinar la relación entre las estrategiasfinancieras aplicadas por las PYMES del sector metalmecánico petroleroy su competitividad empresarial del municipio Lagunillas. La investigación escorrelacional con un diseño no experimental, transeccional - descriptivo decampo. La población fue de 11 gerentes. Se emplearon dos cuestionarios, validadosa través de la técnica de juicio de expertos y la cuantitativa de Cronbacharrojando 0,86 y 0,84 respectivamente. Para el cálculo de correlación se utilizóSpearman Brown obteniendo un coeficiente de 0,768. Se concluyo que estasempresas carecen de estrategias financieras que les permita tener ventajas competitivas.AbstractThe main target of this article is to determine the relation between the financialstrategies applied by SAMEs in the petroleum-related metallurgy sectorand their business competitiveness in the Lagunillas municipality. The researchis correlational, with a non-experimental, trans-sectional-descriptive, field design. The population consisted of eleven (11) managers. Two questionnaireswere used, validated by expert judgment and Cronbach’s quantitative measurement, producing 0.86 and 0.84, respectively. To calculate the correlation, Spearman Brown was used, obtaining a coefficient of 0.768. Conclusions are that these companies lack financial strategies that allow them to have competitive advantages.